PENERAPAN LOGIKA FUZZY TSUKAMOTO DALAM OPTIMALISASI PERSEDIAAN MINYAK PELUMAS KAPAL KARGO CURAH - Melania Fitri Ariyanti; Aditya Maharani; Devina Puspita Sari (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2022)
Lubricating oil vessel is a component that is essential for the smooth and operational cruise ships in the machine maintenance .The shipping companies that still do a rough guess to supply demand lubricating oil must have ripe for calculation based on a voyage made in supply , and from year to year lubricating oilprice increases , who is influential on the operational expenses costs .This research aims to obtain the lubricating oil the optimum route a to b in one trip and knows how the cost savings of the lubricating oil. Methods used in this research is fuzzy tsukamoto .The result showed 2054 liters per trip on ME and 1284 liters on AE engine the forecasting mape 7,3 %and 9,5 % .The cost of purchases demand lubricating oil on a ME engine save Rp .80.837.330 and machinery ae Rp. 53,065,812.95This research contributed to optimal lubricating oil demand in shipping per trip.